Prostokątny Ruszt Plaski Wsparty w Czterech Narożach na Sztywnych Podporach - Cieślak, K. (Engineering Transactions, 1967)
The problem solved is that of determing the deflections and the generalized forces in the bars of a rectangular orthotropic grate resting on rigid supports at the corners. Assuming that the number of bars is larger than five in both directions and that their torsional rigidity is low and may, therefore, be rejected, the problem is reduced to the discussion of an orthotropic plate with zero torsional rigidity. The equation of the deflection surface is derived. The expression obtained is a sum of three components (5.1). A numerical example is given for a grate loaded by a concentrated force P. The bending moment is determined in the cross-section passing through that force. An accuracy sufficient for practical purposes is achieved by taking three terms of the series w1 (2.34) and two terms of the series w0 (4.8) and w2 (2.16).